Beethoven reading music in front of mural - Russia? : s.n. (2026)
Postcard depicting reproduction of the painting by Hans Temple of Beethoven composing, with ghostly figures in the background. Title in Cyrillic. Numbered 11256. Handwritten insciption in Russian on verso. 1 postcard : black and white ; 8.5 x 13.75 cm. (3.5 x 5.5 in.).